Daddy, What's Next? The effect of paternalist leadership on perceived uncertainty in organizations which had gone through merger or acquisition. - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
Leadership has been subject to so many studies examining the high performing organizations in literature. Besides leadership style, cultural competitiveness is emphasized as another high performing factor in literature. Within the framework of merger acquisition, our study focuses on the notion that paternalist leadership negatively effects perceived uncertainty. The survey of this study is conducted on 118 white collar employees in performing banks which had gone through merger or acquisition in Turkey. The obtained data from the questionnaires are analyzed through the SPSS statistical packaged software. Analyses result revealed that the dimensions of paternalist leadership negatively effects perceived uncertainty. There is also some significant evidence on demographic variables. It was seen that male employees perceive their leaders more paternalistic than female employees. Employees are found to perceive more uncertainty than managers. Employees who have female managers perceive more paternalistic leadership than the ones who have male managers.
Keywords: Merger or acquisition; Leadership styles; Paternalist Leadership; Uncertainty; COMMUNICATION